Comparative Analysis of the Technical Efficiency of Different Production Systems for Rice Farming in Eastern Thailand - Chanhathai Kerdsriser; Suneeporn Suwanmanee; Panya Mankeb (My University, 2018)
Background and Objective: Generally, there are three different rice farming production systems: Farming under the agriculture network, conventional organic rice farming and chemical rice farming.This study estimated the technical efficiency (TE) of different production systems for rice farming in eastern Thailand.Materials and Methods: Chachoengsao and Prachinburi were selected as the study areas.Farm-level data were collected during the 2016-2017 production period from 150 respondents consisting of 58 organic farmers under the Alternative Agriculture Network (AAN), 42 conventional organic rice farmers and 50 chemical rice farmers.A stochastic frontier analysis was employed to analyze the survey data.Results: The results indicated that the technical efficiency scores for organic rice farmers under the AAN had the highest level of efficiency compared to conventional organic rice and chemical rice farmers.The average TE of the farmers under the AAN was approximately 0.733, ranging from 0.375-0.940,while the average TE of the conventional organic rice farmers was approximately 0.669, ranging from 0.103-0.948and the average TE of the chemical rice farmers was approximately 0.688, ranging from 0.293-0.999.The results indicate that farmers should use high-quality seeds and organic fertilizer to improve the efficiency of organic rice.Conclusion: The findings indicated that the technical efficiency scores for organic rice farmers under the AAN had the highest level of efficiency comparing to conventional organic rice and chemical rice farmers.
Keywords: Rice farming; Efficiency Analysis Using DEA